Review of promotion of physical activity and health-related factors during pandemic for children and adolescents - Haemi Jee (Tehran University of Medical Sciences, 2021)
Background: Regularly performed physical activity promote proper development and prevent health risk factors in children and adolescents. Pandemic crisis has been limiting the scope of movement with social distancing for participation of physical activity for health promotion. This study aimed to review studies on promoting physical activity to prevent health risks for children and adolescents since the onset of COVID-19.   Methods: Three major online databases (PubMed, Medline, and Scopus) were searched for 'physical activity,' 'intervention' for children and adolescents. Seven articles were selected from 1,761 articles through the inclusion and exclusion processes. Results: All studies were conducted through online. One study showed that streaming services and online apps majorly promoted MVPA (moderate-to-vigorous physical activity), MSE (muscle-strengthening exercise), or combined (MVPA, MSE) by 2.4, 3.1, and 4.3 folds, respectively. Another study showed that greater duration of physical activity (PA) prevented depressive symptoms during exposure to outbreak. Five intervention studies which used digital platforms to promote PA significantly encouraged PA along with the physiological, psychosocial, and academic achievement outcomes. Conclusion: Internet-based digital platforms may assist to promote physical activity for improved psychosocial and academic achievement in children and adolescents during the untack period. Structured PA promotion platforms with various health outcomes for children and adolescents should be developed and scientifically evaluated.